PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN AKTIVITAS BELAJAR PADA PEMBELAJARAN IPS SISWA SEKOLAH DASAR - Fahzia Rahma; Yanti Yandri Kusuma; Melvi Lesmana Alim; Syahrial; Yenni Fitra Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this study is the low level of student learning activity in social studies lessons at UPT SDN 007 Bangkinang, as indicated by the lack of active participation by students, such as asking questions, expressing opinions, and discussing. This study employed the Classroom Action Research (CAR) method, conducted in two cycles, each consisting of two sessions. The instruments used in this study included observation sheets for student activities, teacher activities, and achievement tests. The results showed an increase in student learning activities from the pre-cycle to cycle II. In the pre-cycle, only 22% of students achieved the mastery category. After implementing the CTL model, there was a significant increase in cycles I and II, with an increase in student activity in learning activities. The CTL model proved capable of creating contextual, interactive learning and encouraging students to connect the material with their real-life experiences. Thus, it can be concluded that the implementation of the Contextual Teaching and Learning model can increase student learning activities in social studies learning in grade IV at UPT SDN 007 Bangkinang.